Effects of Multimodal Association on Ambiguous Perception in Binocular Rivalry. (September 2019) - Kim, Sungyong; Kim, Jeounghoon
When two eyes view dissimilar images, an observer typically reports ambiguous perception called binocular rivalry where the subjective perception fluctuates between the two inputs. This perceptual instability is often comprised of exclusive dominance of each image and a transition state called piecemeal state where the two images are intermingled in patchwork manner. Herein, we investigated the effects of multimodal association of sensory congruent pair, arbitrary pair, and reverse pair on piecemeal state in order to see how each level of association affects the ambiguous perception during binocular rivalry. To induce the multisensory associations, we designed a matching task with audiovisual feedback where subjects were required to respond according to given pairing rules. We found that explicit audiovisual associations can substantially affect the piecemeal state during binocular rivalry and that this congruency effect that reduces the amount of visual ambiguity originates primarily from explicit audiovisual association training rather than common sensory features. Furthermore, when one information is associated with multiple information, recent and preexisting associations work collectively to influence the perceptual ambiguity during rivalry. Our findings show that learned multimodal association directly affects the temporal dynamics of ambiguous perception during binocular rivalry by modulating not only the exclusive dominance but also the piecemeal state in a systematic manner.